Analysis of the Impact of ChatGPT Usage and Digital Competence on the Development of Innovative Ideas in MSME Management - Cahyono, Puguh; Aisya, Nur; Kurnia, Auliah Riska; Abdillah, Ikhlas; Syihab, A. Alwi (PT. LITERASI SAINS NUSANTARA, 2024)
The development of digital technology has transformed various aspects of life, including the business and management sectors. ChatGPT, a natural language-based artificial intelligence model, has significant potential in assisting MSMEs in managing various aspects of their business. This study aims to provide a deeper understanding of the impact of ChatGPT usage and digital competence on the development of innovative ideas in MSME management. This research is a literature review with a qualitative approach. Data were collected from scholarly articles published on Google Scholar from 2018 to 2024. The study results indicate that the use of ChatGPT and the enhancement of digital competence have a significant impact on the development of innovative ideas in MSME management. Through case studies of Warung Pintar, Go-Food, TaniHub, and Tokopedia, it is evident that digital technology and artificial intelligence can improve operational efficiency, expand market reach, and increase customer satisfaction. Adequate digital competence enables entrepreneurs to maximize the use of this technology, resulting in relevant and beneficial innovations for their businesses.